Optical tomography system using Charge-Coupled Device for transparent object detection - Juliza Jamaludin; Rahim R.A.; Rahiman M.H.F.; Wahab Y.A.; Rohani J.M.; Sahrim M.; Wan Zakiah Wan Ismail; Irneza Ismail; Balakrishnan S.R. (Penerbit UTHM, 2024)
Indexed by Scopus